Rorschach index of depression and social disability in adults with depressive disorders - Maricela Alfonseca Guerra; Pedro Fernández Olazábal (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2020)
The Rorschach Psychodiagnosis is a projective test that is applied in the evaluation of personality and psychopathological disorders. It was an applied, descriptive-cross-sectional research with a quantitative approach, between 2015 and 2018. This text aims to analyze the frequency of the variables of the Depression Index and the Social Disability Index in protocols for adults with depressive disorders residing in the Camagüey province. The 210 protocols belonging to subjects with depressive disorders that made up the sample were intentionally selected in a pure, non-probabilistic manner. In most protocols, the Depression Index was not effective in diagnosing subjects' depression, and the Social Disability Index was positive. The most frequent variables in the Depression and Social Disability Index indicate the presence of poorly developed cognitive activity, low sensitivity to one's personal world and the environment, as well as difficulties in the sphere of interpersonal relationships. The study responds to the Hermann Rorschach Honorary Chair at the University of Camagüey.